Diplomata mais amante do seu paiz que das suas commodidades : atuação de Francisco Adolfo de Varnhagen nas Repúblicas do Pacífico 1863-1865 - Miranda, José Augusto Ribas (2013)
This dissertation aims to analyze the performance of Francisco Adolfo de Varnhagen as a diplomat in the republics of Peru, Chile and Ecuador from 1863 to 1865. In this period, the brazilian diplomat had engaged in important events like the American Congress of Lima in 1864 and the Hispanic South American war, which put Spain versus Peru, Chile, Ecuador and Bolivia between 1865 and 1866. Looking after to maintain a positive image of the Empire among its neighbors, Varnhagen acted at a time of reorientation of imperial foreign policy throughout the nineteenth century: from Europe to America. His diplomatic activity was analyzed under the light of his values of truth, justice and fairness, also business of his historian craft. From the exposition of these principles dear to the historian-diplomat, the work follows his diplomatic trajectory analyzing the republics of the Pacific.